FASHION AS A FORM OF SELF-IDENTITY ON STUDENTS OF THE STATE UNIVERSITY OF SURABAYA: fashion, identity formation, students - Abisya, Nauval Daffa (The Commercium, 2022)
This research on identity formation through the fashion worn is intended to describe how students, especially in this study, identify themselves through clothing. In this case, fashion or clothing is interpreted as a non-verbal communication because there are messages and impressions that the wearer wants to convey. This research is a qualitative research using the phenomenological method which has the aim of observing and understanding the essence of a clothing phenomenon used by students and facilitating research in terms of data collection. Data collection was carried out through the stages of observation and interviews. The results of this study indicate that the identity formed through clothing occurs because the wearer deliberately regulates and cares about his appearance in social life. This study looks at the concept of dramaturgy as the basis for identity formation through the clothes worn by Unesa students by looking at all the preparation and understanding behind it to help the process of that formation. Fashion in this study was used because the wearer wanted an identity that seemed relaxed, easy to get along with, and friendly to be easily accepted by the environment.